2014
DOI: 10.1364/ol.39.006620
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-fast and calibration-free temperature sensing in the intrapulse mode

Abstract: Ultra-fast and calibration-free temperature sensing in the intrapulse mode A simultaneously time-resolved and calibration-free sensor has been demonstrated to measure temperature at the nanosecond timescale at repetition rates of 1.0 MHz. The sensor benefits from relying on a single laser, is intuitive and straightforward to implement, and sweeps across spectral ranges in excess of 1 cm -1 . The sensor can fully resolve rovibrational features of the CO molecule, native to combustion environments, in the mid-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The measured on-axis cavity FSR, determined from the cavity fringes and the previously determined tuning range, is consistent with the calculated value of 2964 MHz. For pulse repetition rates between 100 kHz -1.5 MHz, the measured tuning range follows the trends described by Chrystie et al [11], as illustrated in Fig Chemical processes in RCM experiments generally occur on the millisecond time-scale; therefore, a repetition rate of 100 kHz would result in a sufficiently high measurement time resolution (10 μs) while also providing a higher tuning range. Although a 50% duty cycle may seem to be the optimal operating point from Fig.…”
Section: Pulsed-qcl Characteristicssupporting
confidence: 74%
See 1 more Smart Citation
“…The measured on-axis cavity FSR, determined from the cavity fringes and the previously determined tuning range, is consistent with the calculated value of 2964 MHz. For pulse repetition rates between 100 kHz -1.5 MHz, the measured tuning range follows the trends described by Chrystie et al [11], as illustrated in Fig Chemical processes in RCM experiments generally occur on the millisecond time-scale; therefore, a repetition rate of 100 kHz would result in a sufficiently high measurement time resolution (10 μs) while also providing a higher tuning range. Although a 50% duty cycle may seem to be the optimal operating point from Fig.…”
Section: Pulsed-qcl Characteristicssupporting
confidence: 74%
“…Three considerations need to be made: 1) sufficient measurement time resolution for chemical processes in the RCM; 2) spectrally resolved CO absorption line-shapes at high pressures (P ~10 bar); 3) cavity coupling noise suppression via chirp-induced laser line broadening. Chrystie et al [11] had previously shown that for pulsed QCLs, the tuning range decreases with increasing repetition rate, and a maximum tuning range is obtained at 50% duty cycle for a specified repetition rate. A similar characterization of tuning range was performed for the QCL used in this work.…”
Section: Pulsed-qcl Characteristicsmentioning
confidence: 99%
“…Temperature sensors based on tunable diode-laser absorption measurements have been widely applied in the investigation of plasma [4,5] and combustion processes (see, e.g., Refs. [6][7][8][9][10][11]), whereby the great majority of works focusses on gases at elevated temperatures. Farooq et al, for instance, applied a continuous-wavelength diode laser to measure time-histories of CO 2 gas temperature at typical combustion temperatures (400-1100 K) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently in our group, temperature diagnostics based on pulsed mid-infrared QCLs were demonstrated with a high temporal resolution in both shock tube [17,18] and RCM experiments [19]. For the shock tube application, Chrystie et al developed a temperature diagnostic by accessing multiple H 2 O lines with a single QCL [17].…”
Section: Introductionmentioning
confidence: 99%